2013
DOI: 10.1111/1365-2664.12163
|View full text |Cite
|
Sign up to set email alerts
|

Improving the application of long‐term ecology in conservation and land management

Abstract: Summary1. Significant effort is being made to develop more inclusive and systematic decision-making frameworks in ecology, but these have yet to include palaeoecology. Doing so would address critical questions about long-term ecological processes (spanning >50 years). 2. This paper outlines the main barriers to the integration of long-term ecological data (LTE) into management. Using two UK upland case studies, it uses a choice experiment to assess the value placed on LTE by ecological researchers, policymaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…We recommend that care should be taken when assessing effectiveness of present and future management decisions, as time delays between policy development, implementation of conservation measures and expected results may occur. Thus, development of conservation programs often based on spatial analysis of a snapshot of changing agricultural landscapes should also consider their history (Davies et al, 2014). Reconstructing historical patterns and processes seems a way to better understanding how present conditions came about, how ecosystems function and should benefit long-term conservation and restoration planning.…”
Section: Resultsmentioning
confidence: 99%
“…We recommend that care should be taken when assessing effectiveness of present and future management decisions, as time delays between policy development, implementation of conservation measures and expected results may occur. Thus, development of conservation programs often based on spatial analysis of a snapshot of changing agricultural landscapes should also consider their history (Davies et al, 2014). Reconstructing historical patterns and processes seems a way to better understanding how present conditions came about, how ecosystems function and should benefit long-term conservation and restoration planning.…”
Section: Resultsmentioning
confidence: 99%
“…In responding to climate change, there is a particular need for climate change‐integrated conservation strategies (Butchart et al., ; Luo et al., ; Schloss et al., ; Willis et al., ). Many studies on this issue have suggested that climate influences local species abundance, community structure and biodiversity, phenology, and species range, but only a few have addressed their research using a historical perspective (Ban et al., ; Beaugrand, Edwards, Raybaud, Goberville, & Kirby, ; Davies et al., ; Mathur & Padalia, ; McClenachan et al., ; Rick & Lockwood, ; Saikia, Kalita, & Saikia, ). We suggest that conservation strategies based on historical information may provide a more realistic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research have highlighted multiple data resources that can be used to collect long‐term historical data, including gazetteers, journal articles, nature reserve surveys, and news (Yang et al., ; Zhang et al., ). In addition, previous research revealed that quantitative analyses are useful for assessing the utility and potential limitations of historical data to develop a roadmap for understanding the population size changes over time (Boshoff & Kerley, ; Channell & Lomolino, ; Davies et al., ; Hortal, Jimenez‐Valverde, Gomez, Lobo, & Baselga, ; Rick & Lockwood, ; Turvey et al., ; Yang et al., ; Zhang et al., ). However, finding complete datasets containing high‐quality information on the spatial distribution of biodiversity indicators within a region over time is difficult (Davies et al., ; Hortal et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, insights into key properties of biodiversity-for example, ecosystem structure and composition in the absence of human modification, or the specific ecological requirements of threatened species now restricted to remnant distributions in potentially suboptimal habitat-will remain incomplete and biased by an "extinction filter" if only assessed using modern-day data (Balmford 1996). There is therefore 28 increasing awareness of the need for a new discipline of 'conservation palaeobiology' that integrates a range of long-term archives into conservation research and management, to identify past environmental baselines and provide novel insights into regional biodiversity, extinction dynamics and ecosystem properties that are unavailable from short-term studies (Bonebrake et al 2010;Rick and Lockwood 2013;Davies et al 2014;Barnosky et al 2017). …”
Section: Conservation Palaeobiologymentioning
confidence: 99%